Influência de um pesticida sobre girinos nectônicos em mesocosmos - BORGES, Brena Márcia de Freitas (2012)
The consequences of repeated applications of pesticides in relatively low concentrations to develop tadpoles can be very negative, but were still slightly evaluated. In this study we used the nektonic tadpoles Dendropsophus minutus Peters, 1872 in 32 artificial ponds (8 replicates per treatment) to evaluate the influence of a pesticides commonly used in agricultural fields in Maranhão, northeastern Brazil. Nymphs of dragonflies have colonized some tanks, but its presence did not differ significantly between tanks of different treatments had no effect as a covariate in the analyses. We tested the effect of different concentrations of Paration Metílico (zero for the control, 0,04µg L-1; 0,1µg L-1; 0,2µg L-1), using the commercial formulation Mentox 600, with an overcoating with 10 days apart. Survival andsize (snout-vent length and mass) of metamorphs did not differ significantly among treatments. But time to metamorphosis was longer on tanks with the higher concentration of the pesticide (ANCOVA: F3, 21= 3,777; p=0,026) in relation to tanks with the intermediate concentration. This longer time to metamorphosis can be a risk to populations that inhabit temporary ponds. Deformed metamorphs occurred in tanks with pesticide, as the death of tadpoles on metamorphosis probably due to problems on limbs and drowning.